Foetal Cell Transplantation for Parkinson’s Disease: Focus on Graft-Induced Dyskinesia - Elisabetta Tronci; Camino Fidalgo; Manolo Carta (Parkinson's Disease)
Transplantation of dopamine- (DA-) rich foetal ventral mesencephalic cells emerged as a promising therapy for Parkinson’s disease (PD), as it allowed significant improvement of motor symptoms in several PD patients in open-label studies. However, double-blind clinical trials have been largely disappointing. The general agreement in the field is that the lack of standardization of tissue collection and preparation, together with the absence of postsurgical immunosuppression, played a key role in the failure of these studies. Moreover, a further complication that emerged in previous studies is the appearance of the so-called graft-induced dyskinesia (GID), in a subset of grafted patients, which resembles dyskinesia induced by L-DOPA but in the absence of medication. Preclinical evidence pointed to the serotonin neurons as possible players in the appearance of GID. In agreement, clinical investigations have shown that grafted tissue may contain a large number of serotonin neurons, in the order of half of the DA cells; moreover, the serotonin 5-HT1A receptor agonist buspirone has been found to produce significant dampening of GID in grafted patients. In this paper, we will review the recent preclinical and clinical studies focusing on cell transplantation for PD and on the mechanisms underlying GID.